Relations between Vitamin B6, Tryptophan Metabolites, and Inflammation. - Reginaldo, Christina. (2017)
Abstract: Background: A variety of inflammatory conditions, including cardiovascular disease (CVD) and diabetes, and are associated with both increased kynurenine pathway (KP) activity and low plasma concentrations of pyridoxal 5'phosphate (PLP), the bioactive form of vitamin B6. Inflammatory cytokines induce the first enzyme in the KP; downstream enzymes require PLP as a cofactor to produce immunomodulatory kynurenine metabolites. We hypothesize low plasma PLP observed during inflammation is due to increased PLP utilization by KP enzymes during inflammation. This PLP depletion may lead to health conditions related to PLP-dependent functions such as hemoglobin and neurotransmitter synthesis. Four studies were conducted to examine the relation between PLP, kynurenine metabolites, and inflammation in the context of cardiovascular disease, anemia, diabetes, and cognitive and psychological function. Methods: Secondary data analyses were conducted on data from Framingham Heart Study Offspring Cohort and Nutrition Aging and Memory in Elders (NAME) cohorts, separately. As an ancillary to NAME, kynurenine metabolites were measured in plasma samples using LC-MS/MS. We similarly measured kynurenine metabolites in plasma, aortic, and lymph node tissues from a porcine model of atherosclerosis to assess the effect of diet and statin use on PLP, kynurenine metabolites, and inflammation. Results: CVD status and plasma PLP were interactive predictors of anthranilic acid concentration: and 2-fold increase in plasma PLP resulted in 1.06 fold change in plasma anthranilic acid concentration among CVD-free subjects. CVD was associated with higher prevalence of plasma PLP insufficiency (PLP<30nmol/L) but not kynurenine metabolite concentrations. Subjects with PLP insufficiency had greater plasma hydroxyanthranilic acid compared to normal (23%, p=0.02). Anemia prevalence was dependent on both plasma PLP and CRP concentrations: it was highest among those in first PLP tertile category with plasma CRP > 10mg/L. Diabetics had lower plasma PLP and higher xanthurenic acid concentrations than non-diabetics. Plasma PLP and xanthurenic acid concentrations were interactive predictors of insulin resistance as measured by HOMA2-IR. PLP insufficiency and the highest plasma concentrations of xanthurenic acid were associated with the highest insulin resistance. Plasma PLP was associated with the attention function of cognition, but kynurenine metabolites were not associated with any domains of cognition or depression. In a porcine model of atherosclerosis, data were inconclusive. Since we did not observe the expected change in inflammation due to diet or statin use, there were no discernable effects of diet or statin use on kynurenine metabolites in plasma, aortic, or lymph node tissues. Conclusions: This project demonstrated that anemia is associated with both inflammation and PLP insufficiency. Our findings suggest inflammation associated PLP insufficiency may increase risk of negative health outcomes comorbid with inflammatory disease. Additionally, we found xanthurenic acid and PLP are interactively associated with HOMA2-IR, indicating KP activation may be involved in inflammatory mechanisms underlying diabetes development. We were unable to observe relations between kynurenines and cognition, depression, diet, or statin use. Ultimately, we were unable to observe increased KP activation at sites of inflammation as an underlying cause of inflammation-associated PLP depletion in the context of these conditions. Associations between kynurenine metabolites and inflammatory conditions studied here suggest a more complex relation may underlie these physiologic changes than previously expected.; Thesis (Ph.D.)--Tufts University, 2017.; Submitted to the Dept. of Nutritional Epidemiology.; Advisor: Jacob Selhub.; Committee: Ligi Paul, Paul Jacques, and Dayong Wu.; Keywords: Nutrition, and Epidemiology.